Ciclos de formação humana no Colégio Estadual do Campo Iraci Salete Strozak - Hammel, Ana Cristina (2013)
This dissertation has as object the deployment process of Cycles Human Formation in the State College Field Iraci Salete Strozak. Its reference to this school today and the need for training and empowerment of rural workers. The MST since its origin in 1984, and the struggle for land, makes the struggle for public school quality, able to contribute to the formation of subjects militants, with the potential to forge a new society. The State College Field Iraci Salete Strozak located in Rio Bonito Iguaçu, in the settlement Marcos Freire, West of Parana, arises from the struggle of the landless and maintains ties with his pedagogy and expresses the tension exerted by the bourgeois state and the right to choose by the appropriate school curriculum demands of rural workers. This research considered the implementation cycles as a form of work organization and pedagogical theoretical bases that underlie their different perspectives on: the Continued Progression Scheme, Learning Cycles and Cycles of Human Formation, which was the choice of school studied. Given the aforementioned context, this research proposes to study the Cycles of Human Formation at school Iraci, guided by the following key issues emerged in the concreteness of our work: what changes are possible in the organization of educational work in cycles based Human Formation, considering the limits of the school? How these changes are linked to a school that contributes the intended formation of the social and announced by MST? In this sense the study allowed us to understand the dimension of collective struggle and contributions of Human Formation Cycles for training of field workers in the class perspective, covering education participatory, emancipatory, incorruptible and quality, with new stories of protagonists. Thus, this thesis is organized into three chapters and, at first, a literature search was based categories and cycles, from authors turned to a historical, cultural and critical on the subject and interfaces with the Political Pedagogical Project (PPP) school studied. In the second chapter, we investigated whether the theoretical assumptions of school organization in cycles, in order to develop an overview from the productions studied and establish relationships with the choice made in the experiment analyzed. In the third chapter sought to identify pedagogical work in the materiality of human MST and announced by the school. Considerations were resumed the summaries constructed throughout the text and the challenges posed by the current corporate model, pointing to the need for progress in attempts to consolidate progressive pedagogical proposals that consider human emancipation.